Turkmen Cultural and Political Movement in Iraq 1968-1980 - محمود, ئاکۆ عبدالکریم; عبدالرحمن, کاروان فتاح (Sulaimani Journal for Humanities, 2025)
The situation of Turkmen, as a resident in southern Kurdistan during the period when the Baath Party took power in Iraq, was politically very difficult and in that period, it was in a real crisis. Although, they did not have an armed political party and did not directly oppose the government, they did not escape from the Baath Party's attempts to marginalize, silence and silence their voices. This study examines the political situation of the Turkmen in the period between 1968 and 1980; the period was the party's strongest period. This study analyzes the political situation of the Turkmens in two sections: The first section was devoted to discussing the official appearance of the Turkmens in a social organization called the Turkmen Brothers Club, and to discuss the conditions of that club in that era, as well as attempts by the Baath party to dominate the club. The second part presents the beginning of the political work of Turkmen in the region and the establishment of their first political party in 1980. In this section, the researcher dealt with analysing all individual and local political attempts.